PERSONAL AND FAMILY FACTORS AS PREDICTORS OF ETNOCENTRISM AND RACISM IN INDIVIDUALS (Heritage, 2024)
The appearance of ethnocentrism and racism in individuals can be analyzed in the context of psychological and social factors. We examine the influence of personal factors through the unique perspective of psychoanalytic theory, with a focus on unconscious processes that influence the appearance of discriminatory attitudes and feelings. We point out the necessity of psychoanalytical work, aimed at raising awareness and transforming defense mechanisms, in order to reduce the prejudices of individuals. From the sociological aspect, it starts from the point of view that attitudes based on ethnocentrism and racism are adopted in the process of socialization, and the most dominant influence is the family, where the child is first informed about society. Using the method of content analysis of theoretical approaches on early socialization and the formation of prejudices towards social groups, the facts that point to the importance of family factors are argued. We conclude that the family, as the primary agent of socialization, has the most potential for combating prejudice by applying educational styles aimed at tolerance and multiculturalism. An integrative approach of psychological and social factors can contribute to the improvement of policies that strive for a solidary and democratic society.
Keywords: racism, ethnocentrism, psychoanalytic perspective, family as primary agent of socialization, combating racism and ethnocentrism, multiculturalism